Immunological Impact of Portal Hypertension and Splenectomy in Living Donor Liver Transplantation. (July 2018) - Taguchi, Kazuhiro; Onoe, Takashi; Hashimoto, Shinji; Tanaka, Yuka; Ohdan, Hideki
Abstract : Background: Recently, an importance of controlling portal vein pressure (PVP) in living donor liver transplantation (LDLT) has attracted more attention. Splenectomy (SPX) is an effective procedure to control PVP, nonetheless, the immunological significance of SPX in portal hypertension remains unclear. In this study, we investigated impacts of PVP and SPX on the anti-donor immune response in LDLT considering the immune relevance of PVP and SPX. Patients and Methods: One hundred and ninety four adult patients underwent LDLT between 2003 and 2015 in Hiroshima University Hospital. We analyzed 132 patients in whom PVP during operation were measured and anti-donor immune responses were routinely monitored by multi-parameter mixed lymphocyte reaction (MLR) assays at 2 weeks after LDLT. We categorized the patients into low (<15 mmHg) and high (≥15 mmHg) PVP groups based on the level of PVP at the end of surgery, and anti-donor responses were compared between two groups. To overcome bias due to the different distributions of covariates in the 2 groups, propensity score matching was performed. Further, we analyzed 86 patients with portal hypertension (≥15 mmHg) at the time of reflow. Those patients were divided into the groups with SPX (n = 20) and without SPX (n = 66) and anti-donor responses were compared between two groups after propensity score matching. Results: In the comparison between low and high PVP groups, 39 matched pairs were selected by the propensity score analysis. MLR assay revealed that the stimulation index of CD8+ T cells which indicates the anti-donor proliferative response and the percentage of CD25+ cells among CD8 T cells which indicates the proportion of activated CD8 T cells were significantly higher in high PVP group than those in low PVP group at 2 weeks after LDLT (P = 0.0016 and < 0.0001, respectively). Furthermore, the incidence of acute rejection episode within 3 months after LDLT was significantly higher in the high PVP group than that in the low PVP group (35.9% vs 15.3%, respectively, P = 0.036). In the comparison of 15 matched pairs between the groups with and without SPX, the stimulation index of CD8+ T cells and the percentage of CD25+ cells among CD8 T cells were significantly lower in the group with SPX (P = 0.0234 and = 0.0243, respectively). On the other hand, in the comparison of 10 matched pairs selected by propensity score matching including PVP level at the end of surgery as factor, the stimulation index of CD8+ T cells and the percentage of CD25+ cells among CD8 T cells were not significantly different between the groups with and without SPX. Conclusions: Results indicate that high PVP at the end of surgery promotes an anti-donor immune-response. Furthermore, SPX suppresses an enhanced anti-donor response in portal hypertension. However, this immunosuppressive effect of SPX might be not due to the direct immunological effect of SPX but due to portal decompression by SPX.